Transformation of Information Systems in the Tasikmalaya City Communication and Information Department - Herlina, Dian; Harits, Benyamin; Mulyana, Yaya (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Statistical data and information regarding government and regional development is a right of the community. But unfortunately, this has not been fully fulfilled in the community. This research then tries to look at the implementation of factors in managing information systems at the Tasikmalaya City Communication and Information Service. This research will be carried out using qualitative methods through case studies. The data used in this study came from observations and interviews. The results of this study then found that the management of information systems at the Tasikmalaya Office was still ineffective. Unprofessional executors and inadequate infrastructure have resulted in this. Several factors that can be useful in supporting information transformation at the Tasikmalaya City Service are data collection, data processing, data analysis and assessment, data presentation and dissemination, and documentation. Some of the inhibiting factors for this transformation are professional staff, infrastructure, and technology.
Keywords: Transformation; Information System; Communication and Informatics Office of Tasikmalaya City